2018
DOI: 10.1155/2018/8350862
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Vaccination Induced TNF-α- and IL-2-Producing T Cell Responses in HIV− Healthy Individuals Higher than in HIV+ Individuals Who Received the Same Vaccination Regimen

Abstract: We investigated cytokine production and expression of degranulation marker CD107a after different strategies of hepatitis B virus (HBV) vaccination in human immunodeficiency virus-infected individuals, which were three doses of 20 μg (standard dose group), four doses of 20 μg (four doses group), or four doses of 40 μg (four double doses group), compared to standard dose vaccination in healthy controls. PBMCs collected at different time points were stimulated in vitro with recombinant hepatitis B surface antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Surprisingly, TNF-a rather than IFN-g is the predominant cytokine secreted in humans after vaccination with the S-based HBV vaccine produced in yeast (38). Arguably, an increase in TNFa-producing T cells may indicate a better immunization outcome in both healthy individuals and risk groups, as recently shown (64,65). Moreover, TNF-a inhibits HBV DNA replication at nontoxic concentrations for the host cell, by a mechanism requiring NF-kBsignaling, which may contribute to an early suppression of HBV infection, should this occur in patients with low anti-HBV antibody titers (66).…”
Section: Discussionmentioning
confidence: 89%
“…Surprisingly, TNF-a rather than IFN-g is the predominant cytokine secreted in humans after vaccination with the S-based HBV vaccine produced in yeast (38). Arguably, an increase in TNFa-producing T cells may indicate a better immunization outcome in both healthy individuals and risk groups, as recently shown (64,65). Moreover, TNF-a inhibits HBV DNA replication at nontoxic concentrations for the host cell, by a mechanism requiring NF-kBsignaling, which may contribute to an early suppression of HBV infection, should this occur in patients with low anti-HBV antibody titers (66).…”
Section: Discussionmentioning
confidence: 89%
“…1 The previous study reported that hepatitis B vaccine can increase the production TNF-α. 14 Nitric oxide can be produced during the activation of macrophages by antigens such as viruses. Nitric oxide is toxic to pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Chawansuntati et al [ 63 ] showed a reduced tumor necrosis factor (TNF)-α and IL-2 Level from CD4+ T cells in HIV-infected patients receiving standard HBV vaccinations and suggested an increased dose or frequency to counter this problem[ 63 ].…”
Section: Hepatitis B Vaccinationmentioning
confidence: 99%